VANESSA AGNEW, SABINE STACH, JULIANE TOMANN, edd., Reenactment Case Studies. Global Perspectives on Experiential History, London and New York 2023, Routledge, 367 s., ISBN: 978-1-138-33396-3 - Wohlmuth, Petr (Dějiny – teorie – kritika, 2024)
Book review